Re-evaluating population-level screening recommendations to address increasing early-onset colorectal cancer rates in Australia: a modelling study☆ - J.-B. Lew; J. Worthington; H. Ge; Q. Luo; E. Feletto; K. Canfell; T. Price (ESMO Gastrointestinal Oncology)
Background: The National Bowel Cancer Screening Program (NBCSP) sends free immunochemical faecal occult blood tests (iFOBTs) to eligible Australians aged 50-74 every 2 years. Rising early-onset colorectal cancer (CRC) rates in people under 50 have raised questions around optimising the NBCSP, contributing to the rationale for updating Australian CRC screening guidelines. To support this, alternative screening age ranges and approaches were evaluated. Methods: A microsimulation model was used to estimate the impact of 2-yearly iFOBT screening starting at age 40, 45 or 50 and/or stopping at 74, 79, or 84 in cohorts with rising incidence rates. Yearly iFOBT screening and 5-yearly stool biomarker testing were also analysed. Results: Lowering screening start ages to 45 or 40 could reduce CRC mortality rates by 5% and 10%, respectively, while extending stop ages to 79 or 85 could reduce CRC mortality rates by 3% and 5%, respectively. Lowering the start age would be more cost-effective and have a more favourable balance of benefits to harms versus raising the stop age. Conclusion: As early-onset CRC rates increase, lowering the screening start age could reduce CRC burden while remaining cost-effective and limiting harms. Based on these findings and implementation considerations, the Cancer Council Australia Colorectal Cancer Screening Working Party determined that 2-yearly iFOBT screening from age 45 to 74 was the most favourable. These analyses supported the 2023 Clinical practice guidelines for the prevention, early detection and management of colorectal cancer: Population Screening, which led to the NBCSP including people aged 45-49 on an opt-in basis from July 2024.